The laser-triggered dynamical plasmonic optical trapping of targets and advanced Raman detection sensitivity. Issue 86 (5th October 2020) - Kang, Yan; Yang, Feng; Wu, Ting; Lu, Siqian; Du, Yiping; Yang, Haifeng
Abstract : Targets can be captured at hot spots during the laser-induced agglomeration of AgNPs via dynamical plasmonic optical trapping. Abstract : A novel method involving the laser-triggered Ag-nanoparticle-based plasmonic optical trapping of targets is developed. This dynamically optimized Raman enhanced protocol exhibits superior detection sensitivity for Serratia marcescens and tetrabromobisphenol A, with LOD values of 5 × 10 5 CFU mL −1 and 6 × 10 −7 M, respectively.